D. D. Palmer (1845-1913) e as origens da quiropraxia no século XIX - Neves, Selma Cosso (2016)
The aim of the present study is to investigate the context and some of the main sources resulting in Daniel David Palmer’s (1845-1913) formulation of chiropractic. Born in Canada, Palmer moved to the United States after the end of the Civil War, a period characterized by severe poverty. The precarious conditions extended also to medicine favoring the development of non-conventional practices, such as Thomson and magnetic therapy, in addition to homeopathic medicine, which had a strong presence in this period. Palmer met Paul Caster (1827-1881), a practitioner of magnetic therapy who treated patients without drugs, but through manipulation only. Interested in Caster’s successful methods Palmer became his disciple and worked for nine years with him. Palmer further founded a small journal, The Magnetic Cure, which served to divulgate his ideas on magnetic therapy. At the same time, strong hints indicate that Palmer devoted himself to a more thorough study of anatomy and physiology, including other sources, as e.g. osteopathy. Palmer finally presented his own healing method in 1895, which he called chiropractic. Also chiropractic dismissed pharmacological treatment, being that diseases were attributed to spine misalignment resulting in compression of nerves and blockade of the vital nervous flow. Many of the reasons that led Palmer to formulate chiropractic are poorly understood and are signaled out and analyzed in the present study